PERANCANGAN DAN IMPLEMENTASI SISTEM MANAJEMEN BISNIS DAN PRODUKSI BUKIK GOMPONG DENGAN PENDEKATAN MULTI ASPEK UNTUK STANDAR RITEL NASIONAL - Albar, Berri Brilliant; Amsal, Ares Albirru (LPPM Universitas Andalas, 2024)
This program aims to develop Bukik Gompong, an organic vegetable and fruit producer in West Sumatra, to meet national retail product standards. The program is designed to enhance the capacity of local farmers through a series of training sessions and mentoring on organic farming techniques, the use of modern agricultural technologies, and effective post-harvest management. Additionally, the program involves collaboration with industry partners like Transmart Carrefour Padang to ensure that the products can be optimally marketed in modern retail markets. The methods used in this activity include identifying market needs, conducting outreach and education for farmers, providing resources such as high-quality seeds and organic fertilizers, as well as offering intensive support during the production and distribution processes. A community development approach was implemented to ensure that farmers were actively involved as key subjects in this business development. The results show a significant improvement in farmers' capacity, both in terms of production management and marketing. Production efficiency also improved with the use of agricultural technologies that support the quality and quantity of organic yields. The collaboration with Transmart Carrefour opened wider market access, allowing local organic products to meet the demand of modern retail markets in West Sumatra. In conclusion, this program successfully created a sustainable business model for the startup while also improving the economic conditions of local farmers. Further recommendations include periodic evaluations and technological innovations to ensure the program’s sustainability.